Reaching for the stars knowledge transfer at PolyU (The Hong Kong Polytechnic University, 2009)
This book introduce about an underdog overtakes, driven to succeed, centres of excelence. IP policy and the importance of protection, seeding entrepreneurs, how innovative marketing leads to commercialization...